Decrease in mortality of adult epilepsy patients since 1980: lessons learned from a hospital‐based cohort. (27th February 2017) - Granbichler, C. A.; Oberaigner, W.; Kuchukhidze, G.; Ndayisaba, J.‐P.; Ndayisaba, A.; Taylor, A.; Bauer, G.; Luef, G.; Trinka, E.
Abstract : Background and purpose: Data on mortality in patients with epilepsy have been available since the 1800s. They consistently show a 2−3‐fold increase compared to the general population. Despite major advances in diagnostic tools and treatment options, there is no evidence for a decrease in premature deaths. The temporal trend of mortality in a hospital‐based epilepsy cohort over three decades was assessed. Methods: A hospital‐based incidence cohort was recruited from a specialized epilepsy outpatient clinic at Innsbruck Medical University between 1980 and 2007, divided by decade into three cohorts and followed for 5 years after initial epilepsy diagnosis. Deaths and their primary causes were determined using probabilistic record linkage with the Austrian death registry. Age‐, sex‐ and period‐adjusted standardized mortality rates (SMRs) were computed in relation to the general population of the same area and grouped according to time of diagnosis. Results: In all, 122 deaths in 4549.9 person‐years (1954.5 women, 2595.2 men) were identified. The overall SMR was 2.2 [95% confidence interval (CI) 1.8–2.6] and decreased from 3.0 (95% CI 2.1–4.3) in 1980–1989, to 2.7 (95% CI 2.0–3.5) in 1990–1999 and to 1.4 (95% CI 1.0–2.0) in 2000–2007. Conclusions: This study indicates a decrease in mortality in newly diagnosed epilepsy patients over the last three decades. This may be due to advances in diagnosis and treatment over the past three decades, including early identification of drug resistance, introduction of new anti‐epileptic drugs and establishment of a comprehensive epilepsy surgery programme in this region.